A Computational Approach for Mapping Heme Biology in the Context of Hemolytic Disorders - Humayun, Farah; Domingo-Fernández, Daniel; Paul George, Ajay Abisheck; Hopp, Marie-Thérèse; Syllwasschy, Benjamin F.; Detzel, Milena S.; Hoyt, Charles Tapley; Hofmann-Apitius, Martin; Imhof, Diana (Frontiers in Bioengineering and Biotechnology, 2020)
Heme is an iron ion-containing molecule found within hemoproteins such as hemoglobin and cytochromes that participates in diverse biological processes. Although excessive heme has been implicated in several diseases including malaria, sepsis, ischemia-reperfusion, and disseminated intravascular coagulation, little is known about its regulatory and signaling functions. Furthermore, the limited understanding of heme’s role in regulatory and signaling functions is in part due to the lack of curated pathway resources for heme cell biology. Here, we present two resources aimed to exploit this unexplored information to model heme biology. The first resource is a terminology covering heme-specific terms not yet included in standard controlled vocabularies. Using this terminology, we curated and modeled the second resource, a mechanistic knowledge graph representing the heme’s interactome based on a corpus of 46 scientific articles. Finally, we demonstrated the utility of these resources by investigating the role of heme in the Toll-like receptor signaling pathway. Our analysis proposed a series of crosstalk events that could explain the role of heme in activating the TLR4 signaling pathway. In summary, the presented work opens the door to the scientific community for exploring the published knowledge on heme biology.